Career trajectories, transition rates, and birthdate distributions: the rocky road from youth to senior level in men's European football - Brustio, Paolo Riccardo; McAuley, Alexander B. T.; Ungureanu, Alexandru Nicolae; Kelly, Adam Leigh (Frontiers in Sports and Active Living, 2024)
This study aimed to assess youth-to-senior transition rates, quantify the magnitude of relative age effect (RAEs), and evaluate how RAEs affect these transitions in 9,527 men's national football players of England, France, Germany, Italy, and Spain. Regardless of national team, only ~15%, 25%, and 40% of U17, U19, and U21 players successfully transitioned to the senior team, respectively, whilst ~14-24% progressed to senior level without being selected during youth. Data suggested a skewed birthdate distribution favouring relatively older players at U17, U19, and U21 levels across all countries, whereas RAEs were also present in England, Italy, and Spain at senior level. Youth-to-senior transition rates were modulated by birthdate at U17 and U19, whereby Q4 players were ~2 and 1.5 times more likely to successfully transition at senior level than Q1 players, respectively. Selection at youth international level does not guarantee selection at senior level, but does make it more likely. Moreover, relatively younger athletes are disadvantaged in youth categories, although are more likely to transition to senior level once they have entered the pathway.